IEI‐EMF provocation case studies: A novel approach to testing sensitive individuals. Issue 2 (10th November 2017) - Verrender, Adam; Loughran, Sarah P.; Anderson, Vitas; Hillert, Lena; Rubin, G. James; Oftedal, Gunnhild; Croft, Rodney J.
Abstract : The etiology of Idiopathic Environmental Intolerance attributed to Electromagnetic Fields (IEI‐EMF) is controversial. While the majority of studies have indicated that there is no relationship between EMF exposure and symptoms reported by IEI‐EMF sufferers, concerns about methodological issues have been raised. Addressing these concerns, the present experiment was designed as a series of individual case studies to determine whether there is a relationship between radiofrequency‐electromagnetic field (RF‐EMF) exposure and an IEI‐EMF individual's self‐reported symptoms. Three participants aged 44–64 were tested during a series of sham and active exposure trials (2 open‐label trials; 12 randomized, double‐blind, counterbalanced trials), where symptom severity and exposure detection were scored using 100 mm visual analogue scales. The RF‐EMF exposure was a 902–928 MHz spread spectrum digitally modulated signal with an average radiated power output of 1 W (0.3 W/m 2 incident power density at the participant). In the double‐blind trials, no significant difference in symptom severity or exposure detection was found for any of the participants between the two conditions. Belief of exposure strongly predicted symptom severity score for all participants. Despite accounting for several possible limitations, the present experiment failed to show a relationship between RF‐EMF exposure and an IEI‐EMF individual's symptoms. Bioelectromagnetics. 39:132–143, 2018. © 2017 Wiley Periodicals, Inc.